2019
DOI: 10.1007/s00170-019-04685-z
|View full text |Cite
|
Sign up to set email alerts
|

Powder interlayer bonding of geometrically complex Ti-6Al-4V parts

Abstract: Powder interlayer bonding (PIB) is a novel joining technique, which has been developed to facilitate high-integrity repairs of aerospace components, manufactured from commonly used titanium alloys. The PIB technique utilises an interlayer between complex geometric components which are mated under pressure and a highly localised heating source. In this study, induction heating enabled bonding in an inert fusion zone by use of an oxygen-displacing shielding gas, with particular attention to the initial heating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, new generation nickel-based superalloys have been specifically designed with increased volume fraction of the second phase strengthening precipitate gamma prime (γ′) (>40%) to meet the high temperature requirements of the engine [ 5 ]. This increased γ′ increases the strength of the alloy but also hinders weldability by making the material prone to microcracking during weld solidification [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, new generation nickel-based superalloys have been specifically designed with increased volume fraction of the second phase strengthening precipitate gamma prime (γ′) (>40%) to meet the high temperature requirements of the engine [ 5 ]. This increased γ′ increases the strength of the alloy but also hinders weldability by making the material prone to microcracking during weld solidification [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Continued growth of the necks requires material to be transported to this region via diffusion mechanisms such as volume and surface diffusion, where vacancies move from the neck region through the powder or along the surface of the powder respectively [33]. As bonding through the intermediate phase progresses, continued plastic deformation densifies the powder interlayer before slowing as the total surface area of the powders reduces until finally ceasing as previously illustrated [32]. Final densification and pore elimination occurs during the final phase where recrystallisation is facilitated by the stored energy introduced during the earlier deformation.…”
Section: Discussionmentioning
confidence: 93%
“…It has already been shown that PIB can be used to provide high-integrity bonds between aerospace alloys [27,[30][31][32]; so, it is no surprise to see high-integrity bonds being produced in the TiAl alloy. The joint is formed through a solid-state sintering process, where the combination of thermal energy and applied load act to consolidate and densify the powder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations